Tonga : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the IMF's projections and estimates on Tonga's real and nominal gross domestic product by sector of origin; production of manufactured goods; tourism statistics; central government fiscal operations and revenue; central government current expenditure by economic and functional classifications; monetary survey; Tonga trust fund; banking survey; accounts of the national reserve bank of Tonga; accounts of the Tonga development bank; balance of payments summary; public debt outstanding; interest rate structure during 1996/97-2000/01; public enterprise sector; and so on.